2001
DOI: 10.1055/s-2001-13778
|View full text |Cite
|
Sign up to set email alerts
|

Introitussonographie in der Inkontinenzdiagnostik. Der Symphysen-Blasenhals-Abstand (SBHA) bei Stress- und Urgeinkontinenz

Abstract: ZusammenfassungFragestellung: Die Messung des Symphysen-Blasenhals-Abstandes (SBHA) mit Hilfe der Introitussonographie ermöglicht eine rasche Beurteilung der gestörten Topographie der Blasenhalsregion bei Stressinkontinenz (SIK) und Descensus genitalis. Es wurde untersucht, ob sich der SBHA von Patientinnen mit Stress-oder Urgeinkontinenz von kontinenten Frauen unterscheidet. Weiterhin wurde der SBHA prä-und postoperativ bei Kolporrhaphia ant. und Kolposuspension nach Burch gemessen. Methode: Bei insgesamt 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
2
1
2
Order By: Relevance
“…Consistent with a loss of anchorage, the bladder neck in these patients descends below the level of the inferior border of the symphysis pubis on straining, resulting in a median difference of height H rest —height H straining of 16 mm. However, unlike Stein and Künzel20, we did not find the preoperative extent of bladder‐neck descent during straining to correlate with the severity of incontinence.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Consistent with a loss of anchorage, the bladder neck in these patients descends below the level of the inferior border of the symphysis pubis on straining, resulting in a median difference of height H rest —height H straining of 16 mm. However, unlike Stein and Künzel20, we did not find the preoperative extent of bladder‐neck descent during straining to correlate with the severity of incontinence.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study stress‐incontinent women showed a more pronounced decrease in H with straining compared with data reported in the literature8, 9, 12, 20. Our preoperative results confirm the observation that bladder‐neck topography is altered in stress‐incontinent women.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nach der klinischen Untersuchung sind besonders die bildgebenden Verfahren wie Ultraschall, Röntgen oder Fluoreszenz geeignet, um Fremdkörper zu diagnostizieren. Zur Inkontinenzdiagnostik kann unter anderem auch die Introitussonographie [17] angewendet werden. Die Extraktion richtet sich nach der Gröûe und Beschaffenheit des Fremdkörpers.…”
Section: Fallberichtunclassified